Composition Analysis of Perforated Concrete Roster Raw Materials To Improve Product Compressive Strength Using Experimental Design Approach - Abdul Mail; Ebang; Nurhayati Fauf; Muhammad Fachry Hafid (Journal of Industrial System Engineering and Management, 2022)
The compressive strength of lightweight bricks produced by CV. Sinar Jaya Maros has a very high variation because there is no standard raw material composition that meets SNI standards, according to SNI 03-0349-1989 that the requirements for hollow concrete bricks for K-350 concrete quality must have a compressive strength of 350 kg/cm2. This research was conducted to design an improvement or quality improvement of hollow concrete brick products in CV. Sinar Jaya Maros. The quality improvement is in increasing the compressive strength of the concrete brick with an optimal composition. Quality improvement was carried out by using the Taguchi method experimental design to obtain the optimal combination of compositions. The orthogonal array notation used is L9(34) with material control factors in the form of cement (A), water (B), and (C), and Casting plaster (D). Data processing is carried out by calculating ANOVA on the average value and S/N Ratio with the best nominal classification. The classification was chosen because the closer to the compressive strength based on the SNI of hollow concrete bricks, the higher the quality of the concrete bricks. This ANOVA calculation is carried out to know which factors have a significant effect on the compressive strength of concrete bricks. The test conducted to determine the quality of lightweight bricks is the compressive strength test of concrete which is carried out using a compression machine. Based on the results of data processing, the ratio of the optimal composition of cement:water: sand was obtained by 2:1:3,5. Confirmation experiments prove that the compressive strength of the composition is robust.